TFEB Probably Involved in Midazolam-Disturbed Lysosomal Homeostasis and Its Induced β-Amyloid Accumulation - Cheng, Dan; Tan, Qilian; Zhu, Qianyun; Zhang, Jiqian; Han, Xiaoyu; Fang, Panpan; Jin, Weilin; Liu, Xuesheng (Frontiers in Human Neuroscience, 2019)
Alzheimer's disease is one of the most common neurodegenerative diseases, β-amyloid play a leading role in the pathogenesis of AD. TFEB, a main regulating factor of autophagy and lysosome biosynthesis, is involved in the pathogenesis of AD by regulating autophagy-lysosomal pathways. To date, the choice of anesthetics during surgery in patients with neurodegenerative diseases and evaluation of the effects and underlying mechanisms in these patients have rarely been reported. In this study, the HEK293-APP cells overexpressing APP and Hela cells were used. The cells were treated with midazolam at different concentrations and different times, then lysosomes were stained by lysotracker and their morphology were observed under a fluorescence microscope. The number and size of lysosomes were analyzed using the imagj j software. The levels of TFEB in the nucleus and APP-cleaved proteins intracellular were detected by nuclear separation and Western Blot. Finally, ELISA was used to detect the levels of Aβ40 and Aβ42 in the cells after drug treatment. We found that 30μM midazolam decreased the number of lysosomes and increased its size in HEK293 and HeLa cells. However, 15μM midazolam transiently disturbed lysosomal homeostasis at 24h and recovered it at 36h. Notably, there was no significant difference in the extent to which lysosomal homeostasis was disturbed between treatments of different concentrations of midazolam at 24 hours. In addition, 30 μM midazolam prevents the transport of TFEB to the nucleus in either normal or starved cells. Finally, the intracellular CTFβ, CTFα, Aβ40 and Aβ42 levels were all significantly elevated in 30μM midazolam-treated HKE293-APP cells. Collectively, the inhibition of TFEB transport to nucleus may be involved in midazolam-disturbed lysosomal homeostasis and its induced β-amyloid accumulation in vitro. The results indicated the risk of accelerating the pathogenesis of AD by midazolam and suggested that TFEB might be a candidate target for reduction of midazolam-dependent neurotoxicity.